Idea wzajemności wobec wyzwań rynku ubezpieczeniowego XXI wieku - Płonka, Maria (The Idea of Mutuality Against the Challenges of Insurance Market of the 21st Century, 2008)
Originally all types of insurance were based on mutuality until when in capitalism period a capital form of insurance appeared. The 20th and 21st centuries have been dominated by capital forms of insurance activities, however the idea of mutuality can be competitive against the capital forms and it has a special place in the sector of social economy. The purpose of the article is to try to define the idea and rules of mutuality, taking into consideration economic realities of the 21st century against the background of retrospectives and present times, taking as an example the analysis of the position of Mutual Insurance Companies (TUW) in Poland. In particular, the idea of mutuality has been analyzed in its legal, marketing, and economic-financial aspects. In conclusion, some perspectives of a development of Mutual Insurance Companies have been defined against the challenges in the insurance market of the 21st century.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 359-367